The Effect of Ascorbic Acid on Mancozeb-Induced Toxicity in Rat Thymocytes - Pavlovic, V; Cekic, S; Kamenov, B; Ciric, M; Krtinic, D (Folia biologica, 2015)
Mancozeb, as a dithiocarbamate fungicide, has been found to exhibit toxicological manifestations in different cells, mainly by generation of free radicals which may alter antioxidant defence systems in cells. The effect of mancozeb on the cells of a primary lymphoid organ has not been studied. In the present study, the effects of mancozeb (0.2, 2 and 5 μg/ml) or mancozeb+ascorbic acid (100 μg/ml), or ascorbic acid alone or control medium alone on the levels of cell viability, apoptosis, intracellular reactive oxygen species production (ROS), mitochondrial membrane potential (MMP) and ATP levels in rat thymocytes were examined in vitro. Cells treated with mancozeb displayed a concentration-dependent increase of hypodiploid cells and ROS production followed by markedly decreased viability of the cells, MMP and ATP levels. Application of ascorbic acid significantly reduced cytotoxicity in cell cultures treated with 0.2 and 2 μg/ml of mancozeb, together with significantly decreased ROS levels and increased MMP and ATP levels. In cells treated with 5 μg/ml of mancozeb, ascorbic acid failed to reduce toxicity while simultaneously increasing the apoptosis rate of thymocytes. These results suggest that ROS plays a significant role in mancozeb-induced toxicity, through alteration of mitochondrial function. Ascorbic acid administration reduced the toxicity rate in cells treated with lower mancozeb concentrations, while it may have the ability to shift cells from necrosis to apoptosis in the presence of highest mancozeb concentrations.
Keywords: Ascorbic Acid; Animals; apoptóza; Antioxidants; maneb; biologické markery; oxidační stres; Rats, Wistar; Biomarkers; Membrane Potential, Mitochondrial; Apoptosis; zineb; Oxidative Stress; Maneb; Reactive Oxygen Species; adenosintrifosfát; thymocyty; kultivované buňky; Zineb; Cells, Cultured; Male; Adenosine Triphosphate; membránový potenciál mitochondrií; antioxidancia; kyselina askorbová; reaktivní formy kyslíku; krysa rodu Rattus; Fungicides, Industrial; Thymocytes; Cell Survival; zvířata; mužské pohlaví; viabilita buněk; průmyslové fungicidy; Rats; potkani Wistar